Interrelationships between students' attitudes toward mathematics, beliefs about mathematics learning, confidence in solving mathematical problems and mathematics performance - Chua, Yi Jiuan (Universiti Malaysia Sarawak, UNIMAS, 2009)
This research examined students’ attitudes toward mathematics, beliefs about mathematics learning, confidence in solving mathematical problems, and mathematics performance. The interrelationships between the variables and the differences in the variables based on gender, race, PMR mathematics grades, attendance at tuition, and assistance from parents in completing mathematics homework were also investigated. One hundred and sixty Form Four students who enrolled in the 2008/2009 academic session from four schools in Kuching were selected as the sample for this study. The Attitudes toward Mathematics Scale and Beliefs about Mathematics Learning Scale were used as the measure of attitudes toward mathematics and beliefs about mathematics learning. The Mathematics Performance Test and Confidence Rating Scale were used to measure students’ mathematics performance and their confidence in solving mathematical problems. Descriptive statistics was used to examine students’ attitudes toward mathematics, beliefs about mathematics learning, confidence in solving mathematical problems, and mathematics performance. Pearson-product moment correlations were used to measure the interrelationships between attitudes toward mathematics, beliefs about mathematics learning, confidence in solving mathematical problems, and mathematics performance while independent t-test and One-Way ANOVA were used to determine the differences in those variables based on gender, race, PMR mathematics grades, attendance at tuition, and assistance from parents in completing mathematics homework. The results indicated that students’ performances in mathematics were average, had positive attitudes toward mathematics, positive beliefs about mathematics learning, and high confidence in solving mathematical problems. The results also showed positive relationship between confidence in solving mathematical problems and mathematics performance. The affective aspects including attitudes toward mathematics, beliefs about mathematics learning, and confidence in solving mathematical problems were interrelated. In relation to the differences in those variables, significant differences were found in confidence in solving mathematical problems and mathematics performance based on race and PMR mathematics grades and not in attitudes toward mathematics and beliefs about mathematics learning. However, no significant differences were found in attitudes toward mathematics, beliefs about mathematics learning, confidence in solving mathematical problems, and mathematics performance based on gender, attendance at tuition, and assistance from parents in completing mathematics homework.